Pengaruh Model TPB Terhadap Penggunaan E-Payment QRIS Pada Generasi Z Di Kota Makassar - Ramadana; Wa Ode Rayyani (CV. ITTC INDONESIA, 2025)
This study aims to determine the influence of attitude, subj subjective norm, and perceived behavioral control on the intention to use QRIS based on the Theory of Planned Behavior (TPB) model among Generation Z in Makassar City. This research adopts a quantitative approach using multiple linear regression analysis. Data were collected from 100 respondents through an online questionnaire. The results indicate that, simultaneously, the variables of attitude, subjective norm, and perceived behavioral control significantly influence the intention to use QRIS. Partially, attitude and subjective norm have a significant effect, while perceived behavioral control does not have a significant effect. The Adjusted R Square value of 28.2% shows that the three variables are able to explain 28.2% of the variation in the intention to use QRIS. This study provides implications for understanding the digital behavior of Generation Z and serves as a reference for payment system developers to enhance the adoption of QRIS among the younger generation.